Peran Digital Marketing dalam Meningkatkan Daya Saing UMKM Kuliner di Indonesia - Deti Kurniati; Heny Fitriani; Sumarno; Ahmad Sofan Ansor; Adhelia Permata Safrina (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to analyze the role of digital marketing in increasing the competitiveness of culinary MSMEs in Indonesia by positioning digital marketing as a strategic process, not just a promotional tool. The study used a qualitative approach, exploring the experiences of culinary MSMEs in utilizing social media, marketplaces, visual content, customer testimonials, and digital communications to reach and maintain markets. Data were collected through interviews and analyzed thematically to identify patterns of digital marketing utilization and their impact on business competitiveness. The results show that digital marketing contributes to increasing MSME competitiveness by expanding business visibility, strengthening customer interaction and trust, as well as the ability to differentiate products and respond to changing consumer preferences. However, digital marketing optimization still faces obstacles such as low digital literacy, inconsistent content production, limited use of customer data, and dependence on digital platform algorithms. These findings confirm that the competitiveness of culinary MSMEs is determined not only by product quality but also by the ability to strategically manage the digital space. This study provides practical implications that strengthening MSMEs needs to be directed at developing sustainable digital capabilities, providing content strategy assistance, and utilizing market data more effectively.